Phytochemicals and bioactivities of Piper betle and Miconia crenata from Sabah, Malaysia - SCHOLASTICA LANTING; CHRISTOPHE WIART; NOR AZIZUN RUSDI (Society for Indonesian Biodiversity, 2026)
Abstract. Lanting S, Wiart C, Rusdi NA. 2026. Phytochemicals and bioactivities of Piper betle and Miconia crenata from Sabah, Malaysia. Biodiversitas 27 (1): d270143. https://doi.org/10.13057/biodiv/d270143. Despite their traditional use, Piper betle and Miconia crenata from Sabah, Malaysia, remain poorly characterized in terms of their phytochemical compositions and bioactivities. The study aimed to compare their antioxidant and antibacterial potential and to identify major bioactive constituents. The dry sample was extracted with hexane, ethyl acetate, methanol, and aqueous solvents. Total phenolic and total flavonoid content were quantified, while antioxidant activity was evaluated using radical scavenging and reducing power assays. Antibacterial activity was evaluated against selected Gram-positive and Gram-negative bacteria, and the chemical composition was profiled by gas chromatography-mass spectrometry (GC-MS). The result showed that methanol extracts exhibited the strongest bioactivity in both species. P. betle methanol extract recorded high total phenolic and flavonoid contents (92.41mg GAE/g DW and 119.92 mg QEg/DW, respectively) and the highest ferric reducing antioxidant power (314 µmol TE/g DW), while its aqueous extract also showed strong reducing capacity (256 µmol TE/g DW). In contrast, M. crenata methanol extract showed high phenolic content (119.92 mg GAE/g DW) with a lower flavonoid level (24.44 mg QE/g DW) and a maximum FRAP value of 217 µmol TE/g DW. The strongest antibacterial activity was observed for P. betle ethyl acetate extract against Acinetobacter baumannii (inhibition zone 15 mm), whereas M. crenata extracts showed only moderate inhibition against Enterococcus faecalis, A. baumannii, and Klebsiella pneumoniae. GC-MS analysis of P. betle methanol extract identified phenolic compounds (chromanol) and sesquiterpenes (β-copaene, seychellene), supporting its superior antioxidant and antibacterial activities. These findings suggest that plants from the Borneo region are a promising source of bioactive compounds with potent antioxidant and antibacterial properties, supporting their potential development into natural medicines.